UNIT 10.9 Preparation of Extracellular Matrices Produced by Cultured and Primary Fibroblasts. Issue 1 (1st June 2016) - Franco‐Barraza, Janusz; Beacham, Dorothy A.; Amatangelo, Michael D.; Cukierman, Edna
Abstract : Fibroblasts secrete and organize extracellular matrix (ECM), which provides structural support for their adhesion, migration, and tissue organization, besides regulating cellular functions such as growth and survival. Cell‐to‐matrix interactions are vital for vertebrate development. Disorders in these processes have been associated with fibrosis, developmental malformations, cancer, and other diseases. This unit describes a method for preparing a three‐dimensional matrix derived from fibroblastic cells; the matrix is three‐dimensional, cell and debris free, and attached to a two‐dimensional culture surface. Cell adhesion and spreading are normal on these matrices. This matrix can also be compressed into a two‐dimensional matrix and solubilized to study the matrix biochemically. © 2016 by John Wiley & Sons, Inc.